Revealing effectiveness and heterogeneity of the impact of China’s coal consumption control policy on air quality - Zhao, Wenjuan; Chang, Miao; Huangfu, Jianhua; Yu, Lei (Frontiers in Environmental Science, 2022)
Whether China's coal consumption control policy (CCCP) improves air quality is controversial. This study used city-level panel data and applied a DID model to identify it. We found that (1) The CCCP has a positive effect on AQI and PM25, which decrease by 7.6327 ug/m3 and 8.4293 ug/m3, respectively, but fails to reduce O3 concentration. (2) The effect of CCCP has regional heterogeneity. The CCCP has not significantly reduced PM2.5 emissions or improved air quality in the PRD region as in the BTHS and YRD regions. Additionally, in the YRD and PRD regions, CCCP can reduce O3 significantly. But the BTHS region failed to reduce the O3, and the introduction of CCCP made the O3 in pilot cities even higher by 4.1539 ug/m3. This study recognized the effects of the CCCP and its regional heterogeneity, which were supportive for policymakers to optimize coal-related policies to ensure environmental sustainability. And we suggested that policymakers should differentiate policies according to regional differences and pay attention to reducing O3 pollution to establish sustainable ecosystems.